2014
DOI: 10.1590/brag.2014.022
|View full text |Cite
|
Sign up to set email alerts
|

Herança da resistência do acesso de melancia PI 595201 a isolado de PRSV-W do Estado do Tocantins

Abstract: ResumoCom o objetivo de identificar o tipo de herança, o número de genes e os parâmetros genéticos e fenotípicos da resistência do acesso PI 595201 a um isolado de PRSV-W da região Norte do Brasil foi conduzido um experimento na área experimental do Departamento de Produção Vegetal da Universidade Federal do Tocantins, em condições de casa de vegetação. A partir do cruzamento entre a cultivar suscetível Crimson Sweet (P 1 ) e o acesso resistente PI 595201 (P 2 ) foi obtida a geração F 1 e as gerações segregant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
(12 reference statements)
0
5
0
1
Order By: Relevance
“…The occurrence prevalence of single and mixed infections of potyvirus PRSV-W, ZYMV and WMV in the State of Tocantins, differed between regions (ALVES et al, 2014). Several studies have shown that PRSV-W has a high incidence in cucurbit crops in the Northeast of Brazil (DO NASCIMENTO et al, 2012.).…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence prevalence of single and mixed infections of potyvirus PRSV-W, ZYMV and WMV in the State of Tocantins, differed between regions (ALVES et al, 2014). Several studies have shown that PRSV-W has a high incidence in cucurbit crops in the Northeast of Brazil (DO NASCIMENTO et al, 2012.).…”
Section: Resultsmentioning
confidence: 99%
“…Variance components Heritabilities (%) It is fundamental to perform the evaluation of the accession reaction with an aggressive and efficient isolate to avoid escape. As well as the parents who will originate the segregating population should be as homogeneous and contrasting as possible (Alves et al 2014). Thus, the results of experiment II proved to be efficient in having homogenous and contrasting parents, which allowed determining that the inheritance is polygenic and controlled by at least nine genes with additive effect and low heritability.…”
Section: Crossingmentioning
confidence: 99%
“…Narrow-sense heritability considers only the additive genetic variance, which is the one that is fixed by selection, which is the most important for the breeder (Ramalho et al 2012). Thus, the magnitude of heritability was low, as seen by Alves et al (2014) working with genetic inheritance to the PRSV virus reaction in watermelon. Thus, breeders should seek recurrent selection as a method to gradually increase the frequency of desirable alleles for the quantitative characteristic, through repeated selection cycles, which favors the increase of narrow-sense heritability (Borém and Miranda 2009).…”
Section: Crossingmentioning
confidence: 99%
“…Inheritance of PRSV-W resistance has been elucidated in other cucurbit crops, such as muskmelons (Pitrat and Lecoq 1983) and watermelons (Azevedo et al 2012, Alves et al 2014. Resistance in C. maxima and C. moschata is controlled by more than one gene.…”
Section: Introductionmentioning
confidence: 99%